2015
DOI: 10.1007/s13277-015-4258-5
|View full text |Cite
|
Sign up to set email alerts
|

RIP1K and RIP3K provoked by shikonin induce cell cycle arrest in the triple negative breast cancer cell line, MDA-MB-468: necroptosis as a desperate programmed suicide pathway

Abstract: Resistance to cell death and reprogramming of metabolism are important in neoplastic cells. Increased resistance to apoptosis and recurrence of tumors are the major roadblocks to effective treatment of triple negative breast cancer. It has been thought that execution of necroptosis involves ROS generation and mitochondrial dysfunction in malignant cells. In this study, the effect of shikonin, an active substance from the dried root of Lithospermum erythrorhizon, on the induction of necroptosis or apoptosis, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…SHK is a naphthoquinone extracted from Chinese herbal medicine plant and is considered to be safe due to its long history use in Chinese traditional medicine. Recent studies confirmed its anti-tumour effects in osteosarcoma46, leukaemia39, colon cancer14, breast cancer16 and glioma19. In this study, we found that SHK suppresses proliferation and induces death in SGC-7901 and BGC-823 gastric cancer cells in dose- and time-dependent manners.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…SHK is a naphthoquinone extracted from Chinese herbal medicine plant and is considered to be safe due to its long history use in Chinese traditional medicine. Recent studies confirmed its anti-tumour effects in osteosarcoma46, leukaemia39, colon cancer14, breast cancer16 and glioma19. In this study, we found that SHK suppresses proliferation and induces death in SGC-7901 and BGC-823 gastric cancer cells in dose- and time-dependent manners.…”
Section: Discussionsupporting
confidence: 76%
“…Necroptosis is a programmed form of necrosis and SHK has been reported as a necroptosis inducer in previous studies161838. Necroptosis is typically inhibited by the blockade of RIPK1.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…22 Previous studies have reported necroptosis as a desperate programmed suicide pathway in breast cancer MDA-MB-468 cells. 23 In fact, necroptosis signaling has been reported to serve as a potent target, and extracts from traditional Chinese medicine have been shown to confer therapeutic efficacy against breast cancer by specifically inducing necroptotic cell death. 24,25 A Smac mimetic also protected against breast cancer via inducing caspase-independent necroptosis.…”
Section: Discussionmentioning
confidence: 99%